Analysis and design of cold-formed steel storage rack uprights under localised fires. (October 2020) - Ren, Chong; Zhang, Peng; Yan, Shen; Dai, Liusi
Abstract: A fire in a storage warehouse creates a scenario that the load bearing members, notably storage rack uprights, are exposed to localised fires, generating the temperature field whose distribution is not uniform along the member length. This non-uniformity in temperature distribution is different from the assumption implied in the current structural fire design guidelines. This paper investigates the resistance of the uprights subjected to localised fires, in particular, fires at the bottom of the uprights, by accounting for the temperature gradients along the member length. Finite Element (FE) models of cold-formed steel storage rack uprights are developed, and are validated against experimental results from aspects of both heat transfer and buckling behaviour. The validated FE models are employed in a parametric study to investigate the resistance and buckling behaviour of the uprights under localised fires. The parametric study results show that the failure modes of the uprights are very sensitive to the localised fires. Moreover, it is observed that the Direct Strength Method (DSM), in the current form, does not produce accurate predictions for the cold-formed steel storage rack uprights under localised fires. Hence, modified DSM global curves are proposed in the paper to allow for the effects of localised fires, and prove to be sufficiently accurate through reliability analysis.